2003
DOI: 10.1189/jlb.1002483
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 modulates dendritic cell function via EP2 and EP4 receptor subtypes

Abstract: We have reported previously that PGE(2) inhibits dendritic cells (DC) functions. Because E prostanoid receptor (EPR) subtypes involved in this action are unknown, expression and functions of these receptors were examined in DC. Western blot and flow cytometry analyses showed that all EPRs were coexpressed in DC. In a dose-dependent manner, lipopolysaccharide (LPS) enhanced EP(2)R/EP(4)R but not EP(1)R/EP(3)R expressions. NS-398, a cyclooxygenase (COX)-2-selective inhibitor, suppressed LPS-enhanced EP(2)R/EP(4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
142
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(151 citation statements)
references
References 53 publications
5
142
2
2
Order By: Relevance
“…It has been shown that induction of cAMP has been associated with the modulatory effects of cAMPelevating agents including db-cAMP, forskolin, and the phosphodiesterase inhibitor IBMX. These reagents inhibited IL-12, TNF-␣, and MIP-1␣, while increasing IL-10 production by BMDCs (22,38,39). A similar effect of cAMP-elevating agents has been reported on BM-derived macrophages (40).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…It has been shown that induction of cAMP has been associated with the modulatory effects of cAMPelevating agents including db-cAMP, forskolin, and the phosphodiesterase inhibitor IBMX. These reagents inhibited IL-12, TNF-␣, and MIP-1␣, while increasing IL-10 production by BMDCs (22,38,39). A similar effect of cAMP-elevating agents has been reported on BM-derived macrophages (40).…”
Section: Discussionmentioning
confidence: 52%
“…PGE 2 is another PG that has anti-inflammatory properties (22,38,49). Similar to the effect of PGI 2 analogs, PGE 2 has been shown to inhibit IL-12, TNF-␣, and IL-6 production by BMDCs, suppress MHC class II expression, and enhance IL-10 production (22,29,38,39). Studies showed that DCs may be activated to produce high levels of proinflammatory cytokines and remain at sites of inflammation or develop into CCR7-expressing cells that allow them to migrate to the draining lymph nodes and induce Ag-specific immune responses (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…In general, EA interferes with synthesis and effects of AA-derived eicosanoids that are probably biologically more active (59). PGE 2 that is derived from AA is generally regarded as pro-inflammatory, but down-regulates IL-12 production of DC (52,58). Hence, a PGE 2 -dependent autocrine negative regulation of DCs may exist (60).…”
Section: Discussionmentioning
confidence: 99%
“…PUFAs, particularly AA, are substrates of COX and LOX for synthesis of eicosanoids (prostaglandins, leukotrienes) that influence DC function (19,57,58). In general, EA interferes with synthesis and effects of AA-derived eicosanoids that are probably biologically more active (59).…”
Section: Discussionmentioning
confidence: 99%
“…PGE2 expressed by antigen-presenting cells is critical in polarizing immune responses [8]. For example, it has recently been reported that PGE2 inhibits activation-induced cell death (AICD) in Th2 cells, thus polarizing adaptive immunity towards a Th1-type response [9].…”
mentioning
confidence: 99%